Study of certain risk factors for anemia during pregnancy (Nouakchott - Mauritania) - SETTY SASS,; MARIEM SIDI MOHAMED,; MARIEM SIDI MOHAMED,; AHMED ZEIN,; AHMED ELBERAE,; ABDERRAZZAK KHADMAOUI,; SOAD KHLLAYOUN,; L. AICHA LRHORFI,; RACHID BENGUEDDOUR, (International Journal of Pharma and Bio Sciences, 2018)
Anemia is one of the most popular public health problems in the world, especially among pregnant women. The objective of our study is to determine the clinical risk factors that influence the severity of anemia in pregnant women. As a result, we conducted a prospective study in the maternity ward of the CHEIKH ZAYED Hospital Center in Nouakchott, during the period from 2015 to 2016. Our sample consists of 400 pregnant women who were interviewed in this study, of which 49,75% (n = 199) were anemic. Of the 199 anemic pregnant women, 11,05% (n = 22) had severe anemia compared to 39,70% (n = 79) with mild anemia. The average age of our sample is 28,09 ± 0,32 years, with a minimum age of 14 years and a maximum age of 45 years. Statistical analyzes show a significant relationship between some clinical factors (age, gestational age, gestational) and hemoglobin levels.